Comparing the performance of using a smart damper in a semi-active suspension instead of a traditional damper using MATLAB/simulink - Ali, Lamyaa Mahdi; Al-Zughaibi, Ali I. (Zielona Góra: Uniwersytet Zielonogórski)
Given the importance of comfort and safety in various driving circumstances, the suspension system emerges as the most crucial component. Two different suspension systems, passive (PSS) and semi-active (SASS), are compared for effectiveness in this research. MATLAB/Simulink is used for simulation, employing a representative two-degree-of-freedom car model to evaluate and compare the performance results of these systems.
Keywords: magnetorheological damper (MR); passive; quarter car; semi-active; system feedback controller